2009
DOI: 10.1590/s0102-311x2009000500007
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização dos medicamentos prescritos aos idosos na Estratégia Saúde da Família

Abstract: IntroduçãoO envelhecimento sempre foi motivo de preocupação para o homem. No entanto, nas últimas décadas, com o crescente aumento da população idosa, tem-se acentuado a busca para compreender esse processo, evidenciar seus problemas e estabelecer propostas para se viver melhor esta etapa da vida.A população idosa brasileira, em 2002, perfazia um total de 14,1 milhões de pessoas. Projetase, para 2025, um total de 33,4 milhões, e entre 1950 e 2025 a população idosa crescerá 16 vezes contra cinco vezes a populaç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
18

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 20 publications
0
7
0
18
Order By: Relevance
“…Studies have demonstrated that gender (females) and age (advanced age) are the most consistent socialdemographic characteristics associated to medication consumption (6,8,12) . The explanation for this positive association between age and higher medication consumption resides in higher occurrences of health problems in more advanced ages, generally long lasting and with higher severity degree, in which treatment and symptoms relief demand pharmacology therapy (6,15) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have demonstrated that gender (females) and age (advanced age) are the most consistent socialdemographic characteristics associated to medication consumption (6,8,12) . The explanation for this positive association between age and higher medication consumption resides in higher occurrences of health problems in more advanced ages, generally long lasting and with higher severity degree, in which treatment and symptoms relief demand pharmacology therapy (6,15) .…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of multiple medications, among the elderly, although needed in many occasions, when inappropriate, may trigger serious complications, often leading to polypharmacy, which is characterized by the simultaneous use of five or more medications (8)(9) . Some authors also define polypharmacy as the use of more medications than what is clinically indicated (6)(7)(8) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(COLOMBO et al, 2004;FARIAS, et al, 2007;MARIN et al, 2008;OLIVEIRA et al, 2009;TAVARES;MUCCILLO-BAISCH, 2008;.…”
Section: Uso E Acesso Ao Programa Farmácia Popular Do Brasilmentioning
confidence: 99%
“…Nos EUA, estima-se que 25 a 32% referentes à totalidade de medicamentos prescritos sejam para utilização em idosos e, este consumo, no Japão, corresponde à aproximadamente 30,6% (OLIVEIRA et al, 2009). …”
Section: Estudo Publicado Por Mclean E Le Couteurunclassified